BARBIE "AN ICON OF PERFECT BEAUTY": POPULAR CULTURE PERSPECTIVES - M. Syaifuddin S. (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
This study discusses about Barbie as an icon of popular culture that is suspected to be a symbol of female perfection. American Studies approach through historical aspects, and the social becomes very important because Barbie was born in American society. Semiotic theory becomes a tool of analysis in this study because the theory is able to explore and discover the meaning of a popular culture artifacts that are being researched through symbols that exist on the Barbie. The results of this study show that icon and popular culture are two things that can not be separated. When a popular cultural artifacts are created, usually always accompanied by a meaning brought or is represented by the artifacts. The results of this study also indicate that Barbie can always reflect popular culture that are popular, so that Barbie can be referred to as an icon of popular culture. In the end, Barbie became an icon created ideal nature of the word "beautiful" in American society.